Effect of nano-sized nickel ferrite addition on superconducting properties of (Tl0.85cr0.15)sr2cacu2o7-? superconductors - Kong W. (Trans Tech Publications Ltd, 2023)
Calcium compounds; Chromium compounds; Copper compounds; Current density; Ferrite; High temperature applications; Iron compounds; Magnetic susceptibility; Nickel; Nickel compounds; Oxide superconductors; Scanning electron microscopy; Solid state reactions; Strontium compounds; Temperature; X ray diffraction; Ac susceptibility; Ac-susceptibility measurements; Close-packed microstructure; Nano-sized nickel; Solid state reaction method; Superconducting properties; Tl-1212; Transport critical current density; Iron-based Superconductors